Late-Life Tourette Syndrome Is a Cause of Unexpected Cursing in the Elderly - Clifford Qualls; Otto Appenzeller (Case Reports in Neurology, 2019)
Tourette syndrome is a tic disorder with onset in childhood. By contrast, we report a new Tourette syndrome with onset in late life. We use statistics to support our contention that this behavioral disorder is a hitherto unrecognized variety of Tourette syndrome. There are three tic disorders distinguished by the types of tics present (motor, vocal/ phonic, or both) and by the length of time that the tics have been present. Individuals with chronic tic disorder have either motor tics or vocal tics which have been present for more than 1 year.